Response of bioregulators and irrigation on plant height of Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
The field experiment was carried out during the 2014-15 and 2015-16 in Rabi season to evaluate the response of bioregulators and irrigation on growth parameters of Indian mustard (Brassica juncea L.). The treatments consisted three irrigation levels (no irrigation, one irrigation and two irrigation) and seven foliar spray of bioregulators (control (water spray), thiourea @1000ppm, thiourea @ 500ppm, salicylic acid @ 100ppm, salicylic acid @ 50ppm, glycinebetaine @ 100ppm and glycinebetaine @ 50ppm). The result indicated that in the irrigated plots significantly improved the plant height of Indian mustard. The application of two irrigation recorded highest plant height at 80 DAS (132.7, 119.9 and 126.3 cm), 100DAS (173.6, 168.5 and 171.1 cm) and at harvest (176.4, 171.9 and 174.2 cm) followed by the application of one irrigation in both years and pooled analysis, respectively. Moreover, the application of bioregulators significantly improves the plant height of the Indian mustard. The application of thiourea @ 1000ppm gave highest plant height at 80 DAS (130.5, 118.2 and 124.4 cm), 100DAS (172.4, 166.8 and 169.6 cm) and at harvest (175.3, 170.9 and 173.1 cm). However, the application of thiourea @ 500 ppm was statistically at par with thiourea @ 1000ppm in both years and pooled analysis, respectively. Furthermore, combined result of bioregulators and irrigation levels were observed significant on plant height of Indian mustard. The application of two irrigation+ foliar spray of thiourea @1000ppm recorded the highest plant height at 100DAS (190.2, 182.3 and 186.3 cm) and at the time of harvest (194.2, 187.6 and 190.9 cm) over control. The application of two irrigation+ foliar spray of thiourea @ 500ppm was statistically at par at 100 DAS (189.4, 181.6 and 185.5 cm) and at harvest (193.3, 186.7 and 190.0 cm) with two irrigation+ foliar spray of thiourea @1000ppm in both years and pooled analysis, respectively. The present study highlighted the practical importance of the irrigation levels and foliar spray of bioregulators combination response on plant height of Indian mustard.